Sustainability Evaluation of Mina Padi Farming in Lebak Swamps Using the MDS Method - Samsul Alam Fyka; Usman Rianse; Lukman Yunus; Muhammad Aswar Limi (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
This study aims to evaluate the sustainability of Mina Padi farming on wetlands in Epeesi Village based on five dimensions of sustainability: economic, social, ecological, institutional, and technological. The research was conducted in 2023 and involved 75 farmers and village heads, farmer group leaders, agricultural extension officers, and the agriculture office. Data analysis used the Multidimensional Scaling (MDS) approach with the Rapfish method to calculate the sustainability index in each dimension. The dimensions used are economic, social, institutional, ecological, and technological. The results showed that Mina Padi farming is quite sustainable, with an overall index of 69.58. The economic, social, and ecological dimensions are in the sustainable category, with an index of 76.59, 78.65, and 84.74, respectively. However, the institutional and technological dimensions are moderately sustainable, with indices of 57.44 and 50.49, respectively. These findings indicate the need for institutional strengthening and adoption of innovative technologies to support long-term sustainability. Efforts to strengthen inter-institutional coordination, improve decision-making capacity, and encourage technological innovation are important steps to improve the sustainability of this system. With these improvements, Mina Padi farming has the potential to become a sustainable agriculture model that can be applied in other regions to support sustainable development globally.